The effects of probiotic treatment with Bifidobacterium breve, Bif195 for small intestinal Crohn’s disease and the gut microbiome: results from a randomised, double-blind, placebo-controlled trial - Ida Marie Bruun Grønbæk; Sofie Ingdam Halkjær; Sarah Mollerup; Esben Holm Hansen; Sarah Juel Paulsen; Sara Engel; Klaus Theede; Rune Wilkens; Trine Boysen; Andreas Munk Petersen (Gut Pathogens)
Abstract Background The aetiology of Crohn’s disease, a chronic inflammatory bowel disease, is multifactorial and not completely understood. However, the association with gut dysbiosis is well-established, and manipulation of the gut microbiota has gained interest as a treatment strategy. This study aimed to investigate the effects of the probiotic strain Bifidobacterium breve, Bif195™ (Bif195) on intestinal inflammation, symptoms, and the gut microbiome composition in patients with small intestinal Crohn’s disease. Methods This was a randomised, double-blind, placebo-controlled trial. Thirty-three patients with small intestinal Crohn’s disease were assigned to eight weeks of treatment with Bif195 or placebo (1:1). The primary outcome was changes in bowel wall thickness measured by intestinal ultrasonography. Other outcomes were changes in symptom severity, quality of life, faecal calprotectin, fatigue, and specific inflammatory parameters on ultrasonography. Changes in the microbiome composition were also examined. Results Bif195 did not affect the bowel wall thickness in the small intestine compared to placebo. Nor did we observe effects on secondary or clinical explorative outcomes. Analysis of the gut microbiome showed that the relative abundance of B. breve rose during the intervention in the Bif195 group, but the result was statistically non-significant. Surprisingly, we observed a clustering of baseline microbiome data into two groups that differed in several aspects including a statistically significant difference in the incidence of previous bowel resections among the participants. Furthermore, changes in symptom scores after eight weeks of intervention were significantly different across the two microbiome groups, with an interaction effect of p = 0.04. Conclusions Eight weeks of treatment with Bif195 did not affect clinical outcomes for Crohn’s disease. However, variations in baseline microbiome data influenced the results. This underscores the importance of assessing baseline microbiome data in intervention studies in Crohn’s disease. Clinicaltrials.gov NCT04842149